Psychopathy, attention, and oddball target detection: New insights from PCL‐R facet scores. (24th April 2015) - Anderson, Nathaniel E.; Steele, Vaughn R.; Maurer, J. Michael; Bernat, Edward M.; Kiehl, Kent A.
Abstract Psychopathy is a disorder accompanied by cognitive deficits including abnormalities in attention. Prior studies examining cognitive features of psychopaths using ERPs have produced some inconsistent results. We examined psychopathy‐related differences in ERPs during an auditory oddball task in a sample of incarcerated adult males. We extend previous work by deriving ERPs with principal component analysis (PCA) and relate these to the four facets of Hare's Psychopathy Checklist Revised (PCL‐R). Features of psychopathy were associated with increased target N1 amplitude (facets 1, 4), decreased target P3 amplitude (facet 1), and reduced slow wave amplitude for frequent standard stimuli (facets 1, 3, 4). We conclude that employing PCA and examining PCL‐R facets improve sensitivity and help clarify previously reported associations. Furthermore, attenuated slow wave during standards may be a novel marker for psychopaths' abnormalities in attention.